Is there an optimal interval for medal winning performance in World Para Powerlifting competition? - Lopes-Silva, J. P.; Richardson, D.; Fukuda, D. H.; Franchini, E. (American Journal of Physical Medicine & Rehabilitation, 2021)
To determine the optimal interval between competitions for success in World Para Powerlifting events. A total of 1,034 female (age: 34.4 ± 9.1 years) and 1,697 male (age: 33.7 ± 8.3 years) competition results from international Paralympic powerlifting events conducted between 2014 and 2020 were analyzed. Odds ratios for preparations intervals between competitive events were evaluated considering the dependent variable, earning a medal, and the independent variable, level of competition. There was an increased probability of winning a medal when the preparation interval was in the range of 22-30 weeks (P = 0.004), as compared to <11 weeks, while competing at World Cup events, whereas for World Championships and Paralympic Games, there was an increased probability of winning a medal when the interval range was 23-31 weeks (P = 0.002) and = 40 weeks (P = 0.011) compared to <23 weeks. However, there was no significant differences between preparation intervals for Regional Games/Championships. The Para Powerlifting athletes participating in the World Cup events, World Championships and Paralympic Games share an optimal interval for success of approximately 21-31 weeks, results from the World Championships and Paralympic Games can also be optimized with interval of =40 weeks.